2023
DOI: 10.1128/msphere.00100-23
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of antimicrobial resistance genes in hospital wastewater using the multiplex hybrid capture target enrichment

Abstract: Wastewater can be useful in monitoring the spread of antimicrobial resistance (AMR) within a hospital. The abundance of antibiotic resistance genes (ARGs) in hospital effluent was assessed using metagenomic sequencing (mDNA-seq) and hybrid capture (xHYB). mDNA-seq analysis and subsequent xHYB targeted enrichment were conducted on two effluent samples per month from November 2018 to May 2021. Reads per kilobase per million (RPKM) values were calculated for all 1,272 ARGs in the constructed database. The monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Similarly, clinically relevant carbapenems ARGs blaNDM-1, blaVIM, blaKPC and blaIMP were only detected by QIAseq xHYB AMR panel, albeit in low abundance (< 0.00001). Similar results were also observed in a study in Japan [22].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, clinically relevant carbapenems ARGs blaNDM-1, blaVIM, blaKPC and blaIMP were only detected by QIAseq xHYB AMR panel, albeit in low abundance (< 0.00001). Similar results were also observed in a study in Japan [22].…”
Section: Resultssupporting
confidence: 91%
“…Based on the proportions of ARGs detected, tetracycline ( abundance (< 0.00001). Similar results were also observed in a study in Japan [22].…”
Section: Abundance Composition and Diversity Of Argssupporting
confidence: 91%
See 2 more Smart Citations
“…It has previously been demonstrated that a variety of in-solution hybridization-based enrichment ( Gnirke et al, 2009 ) designs can increase the sensitivity of HTS for the detection of viruses or bacteria in complex sample matrices ( Christiansen et al, 2014 ; Matranga et al, 2014 ; Bonsall et al, 2015 ; Briese et al, 2015 ; Mate et al, 2015 ; Wylie et al, 2015 ; Brown et al, 2016 ; O'Flaherty et al, 2018 ; Lim et al, 2019 ; Paskey et al, 2019 ; Furtwängler et al, 2020 ; Li et al, 2020 ; Elliott et al, 2021 ; Wylezich et al, 2021 ; Kuchinski et al, 2022 ) although there can also be challenges in terms of false positive identification of pathogens and the bioinformatic methods involved ( Kapel et al, 2023 ). Hybridization enrichment sequencing has also been demonstrated to enrich the sensitivity of detecting antimicrobial resistance genes in wastewater samples ( Baba et al, 2023 ). Here, we extend the application of this strategy to investigate the possibility that a whole genome, targeted enrichment approach could widen the diagnostic window for R. prowazekii and O. tsutsugamushi and, unlike previous studies, including an O. tsutsugamushi study ( Elliott et al, 2021 ) we apply this approach not just to whole genome sequence-based detection and characterization, but also to qPCR-based detection.…”
Section: Introductionmentioning
confidence: 99%